Hubungan Pengetahuan tentang Pangan Halal dan Thoyyib dengan Kebiasaan Makan Mahasiswa Universitas Al-Azhar Indonesia - Puspa, Amalina Ratih; Umami, Zakia; Nurlatifah, Hanny (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2023)
The large muslim population in Indonesia makes the need for halal food and thoyyib increases. This need has not been matched by public awareness in choosing, buying and consuming halal products, especially among students. This cross sectional study aims to analyze the relationship between knowledge of halal food  and thoyyib with the eating habits of Al-Azhar Indonesia University students. The research was conducted from March  to October 2020. The research subjects were 110 active students of Al-Azhar Indonesia University who were  selected by proportional random sampling. Data was collected online using google forms. The results showed that most of the subjects (63.6%) had moderate knowledge of halal and thoyyib food, with a score of 60-80. The results also showed that most of the study subjects (76.4%) had relatively good eating habits (score ≥ 92). There was a significant relationship between knowledge of halal food and thoyyib with the frequency of meals per day (r = 0.834, p <0.05).Keywords - Halal, Thoyyib, Knowledge, Eating Habits, Students.